1986
DOI: 10.1002/masy.19860060123
|View full text |Cite
|
Sign up to set email alerts
|

Anionic polymerization of cyclosiloxanes with cryptates as counterions: New results

Abstract: A kinetic study of the anionic polymerization of hexamethylcyclotrisiloxane ((CH3)2Si0)3 (D3) was carried out in toluene with the cryptate Li+ + 12111 as a counterion. The kinetic order with respect to the living end concentration was found to be equal to 1, and the propagation rate constant relative to cryptated ion pairs was determined at several temperatures between -20 and +20°C. The corresponding activation parameters were calculated : Ep = 9.8 kcal.mo1-1 andThe reaction of 1,3,5,7-tetramethyl-l,3,5,7-tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…With the less polar solvent, toluene, the propagation started with the addition of [12]crown‐4 but proceeded slowly (28% conversion after 108 h). This was contrary to the results of Hubert et al,19 who reported propagation rate constants of the same magnitude for this initiating system for D 3 and D v4. The polymerization rates of n ‐BuLi and (CH 3 ) 3 SiCH 2 Li with crown ether in toluene are comparable.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…With the less polar solvent, toluene, the propagation started with the addition of [12]crown‐4 but proceeded slowly (28% conversion after 108 h). This was contrary to the results of Hubert et al,19 who reported propagation rate constants of the same magnitude for this initiating system for D 3 and D v4. The polymerization rates of n ‐BuLi and (CH 3 ) 3 SiCH 2 Li with crown ether in toluene are comparable.…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, the commercially available D v4 was also chosen as the monomer for the PMVS block and compared with D v3. Because of the smaller ring strain in D v4, the ring‐opening reaction needs additional activation with respect to cyclotrisiloxanes 19, 20. For the anionic ring‐opening of cyclosiloxanes, typically strong bases such as organolithium compounds (e.g., butyllithium) and THF as a solvent to minimize ion–ion interactions between the lithium cation and the silanolate anion are used 21.…”
Section: Resultsmentioning
confidence: 99%
“…2 in comparison with the 4-units monomer. On one hand, propagation rate constants increase with the number of units in the cycles, which is the exact opposite of the trend observed in bulk [24]. A possible explanation lies in the preferential partitioning of large cycles at the interface, where propagation occurs.…”
Section: Homopolymerization Of D 4 V [20]mentioning
confidence: 68%
“…Because the propagation of the chains is reversible also backbiting of active centers with its own chain is possible. Thus, the reaction is a thermodynamically controlled ring-chain equilibration reaction between active linear polymer chains (Cn*) and ring species (Mx) with x monomeric units as described by the Jacobson-Stockmayer theory [33,50,[52][53][54] and shown in Scheme 2. Numerous earlier works [21,26,33,53] have demonstrated that the anionic ROP of cyclosiloxanes can be seen as an excellent model system for this theory.…”
Section: Parameter Evaluation In Model Solution-based Polymerizationmentioning
confidence: 99%